2002
DOI: 10.1093/humrep/17.12.3251
|View full text |Cite
|
Sign up to set email alerts
|

Population variation in age-related decline in male salivary testosterone

Abstract: Age patterns of testosterone decline vary between populations primarily as a result of variation in the peak levels attained in young adulthood. The potential consequences of this variation for other aspects of male health deserve investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
155
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(169 citation statements)
references
References 39 publications
10
155
2
2
Order By: Relevance
“…This problem is particularly acute for small molecules, such as the steroid hormones, present at very low concentrations. Cortisol is present typically at 0.1 -10 ng/mL in human saliva and testosterone at 29-290 pg/mL (Ellison et al, 2002). Measurement in saliva is particularly advantageous as it allows non-invasive detection of small molecules and regular sampling.…”
Section: Measurement In Salivamentioning
confidence: 99%
“…This problem is particularly acute for small molecules, such as the steroid hormones, present at very low concentrations. Cortisol is present typically at 0.1 -10 ng/mL in human saliva and testosterone at 29-290 pg/mL (Ellison et al, 2002). Measurement in saliva is particularly advantageous as it allows non-invasive detection of small molecules and regular sampling.…”
Section: Measurement In Salivamentioning
confidence: 99%
“…Consider the production of estrogens and androgens over the life course. One view is that aging renders men incapable of sustaining androgen production at previous levels, and therefore men reduce androgen production from middle age onwards (Ellison et al 2002). Similarly, menopause renders women incapable of sustaining estrogen production at early adult levels.…”
Section: Adaptations To Agingmentioning
confidence: 99%
“…3 In addition, the T of saliva (Sa-T) is regarded as free testosterone, and its measurement is thought to reflect blood Free-T and Bio-T. 4 It has been reported that Total-T does not vary, but Free-T decreases gradually with aging. 5 Cortisol (F), which is an adrenal cortical hormone, does not show changes in level with aging, but is increased by stress. 6 Cortisol remains constant after increasing during the period of sexual maturation at the same time as T. Cortisol is known to raise blood pressure and blood sugar levels as well as cause sterility and immune dysfunction.…”
Section: Introductionmentioning
confidence: 99%